In Vitro Anticancer Activity of cis-Diammineplatinum(II) Complexes with β-Diketonate Leaving Group Ligands - Wilson, Justin J. (2012)
Five cationic platinum(II) complexes of general formula, [Pt(NH(3))(2)(β-diketonate)]X are reported, where X is a non-coordinating anion and β-diketonate = acetylacetonate (acac), 1,1,1,-trifluoroacetylacetonate (tfac), benzoylacetonate (bzac), 4,4,4-trifluorobenzoylacetonate (tfbz), or dibenzoylmethide (dbm), corresponding respectively to complexes 1–5. The log P values and the stabilities of 1–5 in aqueous solution were evaluated. The phenyl ring substituents of 3–5 increase the lipophilicity of the resulting complexes, whereas the trifluoromethyl groups of 2 and 4 decrease the stability of the complexes in aqueous solution. The uptake of 1–5 in HeLa cells increase as the lipophilicity of the investigated complex increases. Cancer cell cytotoxicity studies indicate that 1 and 3 are the least active complexes whereas 2, 4, and 5 are comparable to cisplatin.